TINGKAT KEKERASAN TERHADAP ANAK JALANAN YANG MENJADI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL - Putrayasa, I Komang; Wairocana, I Gusti Ngurah (Kertha Negara : Journal Ilmu Hukum, 2013)
The level of violence against street children who are victims of sexual abuse crime in terms of criminal law perceptive. To the problem of how to shape the legal protection of street children who are victims of sexual abuse crimes? and how the sanctions against perpetrators of sexual abuse of street children?. The method of writing using descriptive normative methods. The results related to Law No. 23 of 2002 on Child Protection and the Code of Criminal Second Book Chapter XIV: Crimes Against Sexual. World streets filled with violence and exploitation, other forms of violence against street children ranging from the physical, psychological, and sexual violence.
Keywords: Violence, Sexual, Street Children, Child Protection